2009
DOI: 10.2478/s11658-008-0038-1
|View full text |Cite
|
Sign up to set email alerts
|

Homing of annexin-labeled stem cells to apoptotic cells

Abstract: Ischemic diseases are characterized by the presence of pro-apoptotic stimuli, which initiate a cascade of processes that lead to cell injury and death. Several molecules and events represent detectable indicators of the different stages of apoptosis. Among these indicators is phosphatidylserine (PS) translocation from the inner to the outer leaflet of the plasma membrane, which can be detected by annexinV (ANXA5) conjugation. This is a widely used in vivo and in vitro assay marking the early stages of apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Thus far, these probes have been used mainly for cancer imaging, but these techniques can be potentially applied to detect apoptosis after stem cell delivery (63). Interestingly, a recent study demonstrated that conjugation of annexin to stem cells improved homing to apoptotic cells in vitro (64). Further investigation is needed to better define the utility of these techniques for stem cell therapy.…”
Section: Imaging Survival and Engraftmentmentioning
confidence: 99%
“…Thus far, these probes have been used mainly for cancer imaging, but these techniques can be potentially applied to detect apoptosis after stem cell delivery (63). Interestingly, a recent study demonstrated that conjugation of annexin to stem cells improved homing to apoptotic cells in vitro (64). Further investigation is needed to better define the utility of these techniques for stem cell therapy.…”
Section: Imaging Survival and Engraftmentmentioning
confidence: 99%